Aspects of Agricultural Real Estate Management in the Value Approach in Ukraine - Nevesela, Anastasiia (Geomatics and Environmental Engineering, 2019)
The paper discusses aspects of agricultural real estate management according to the value approach in Ukraine. The paper also characterises agricultural lands in reference to their soil classes and acreages. It also discusses the term of tenancy as one of the forms of management of agricultural real estates. The procedure of the determination of the value of agricultural real estates in Ukraine has been also discussed. The paper also presents the conditions of agricultural lands in Ukraine, their acreages and the amount of lands owned by the state and by private owners. The procedure of leasing agricultural lands has been also described.